Penyuluhan Fisioterapi Komunitas Tentang Osteoarthritis Genu kepada Kelompok Prolanis di Puskesmas Tumpang - Luh Putu Gina Safitri; Ninien Febriani; Arys Hasta Baruna (Universitas Muhammadiyah Manado, 2024)
Elderly or elderly is someone who has reached the age of 60 years and over which in general the elderly experience a decrease in endurance so that they are vulnerable to various degenerative diseases such as Osteoarthritis. Osteoarthritis is a type of arthritis that most often occurs especially among the elderly or commonly called degenerative diseases, Osteoarthritis is one of the main causes of morbidity, and physical disability. The method given in community physiotherapy activities is to provide counseling on understanding, causes, signs and symptoms, prevention and exercises. From the activities that have been carried out at the Tumpang Health Center on Saturday, October 19, 2024, it can be concluded that it runs smoothly and is well realized. The benefits of this counseling activity are to provide insight and knowledge about the prevention and treatment of Osteoarthritis or knee arthritis so that the knowledge of the elderly about Osteoarthritis increases.